POLA SENSITIVITAS Eschericia coli TERHADAP ANTIBIOTIK METRONIDAZOLE - Arya Iswara (Universitas Muhammadiyah Semarang, 2015)
Escherichia coli (E. coli) have a potency to be a pathogen bacteria cause an illness. Antibiotic treatments to a patient have a purpose to eliminate the pathogen bacteria. Bacteria resistance to antibiotic was influenced by the intensity of antibiotic treatment in a region, the uncontrolled antibiotics treatments would increase the antibiotic resistance of bacteria. This research was using four different sample, they were feces from diarrhea, ice block, waters from well, and ketchup. Approximately 1 gram from each sample diluted in 10 mL of BHI and then incubated for 6 hours in 37 C. After 6 hours incubations, the samples inoculated in EMBA and incubated in 37 C for 24 hours. The metallic green colored bacteria colony inoculated in Mac Conkey Agar and incubated in 370C for 24 hours. The separated colony sub cultured into HIA and tested using biochemistry test. Sensitivity test conducted using the Kirby Bauer method. The test result showed that 5 samples were sensitive to metronidazole and 26 samples wereresistant to metronidazole.Key word: E.coli, metronidazole, sensitivity.